Sailing Together : A Case Study of Maersk's Diversity, Equity, and Inclusion Policies and Their Influence on Employee Performance and Satisfaction - Machovič, Bernard; Křečková Kroupová, Zuzana, 1972-; Callerová, Monika; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
Diversity, Equity, and Inclusion initiatives have undoubtedly reshaped the current socioeconomic environment in which companies conduct their business. No longer do they need to focus solely on margins and performance indicators. They now must consider factors such as employee satisfaction when making decisions and setting performance goals. But in doing so they receive certain benefits, such as increased employee efficiency, customer satisfaction, and enhanced problem-solving capabilities, while also gaining access to wider talent pools with candidates more likely to apply for vacancies. The main objective of this thesis is to evaluate Diversity, Equity, and Inclusion policies in a specific company and identify their impact on employee performance and satisfaction. Diversity, Equity, and Inclusion is a complex topic on which extensive literature has been written. A review of this literature is provided in the first part of this thesis with a focus on benefits, challenges, and ways of driving positive change in the Diversity, Equity, and Inclusion of a company. The second part of this thesis presents the research in which the theoretical principles of Diversity, Equity, and Inclusion were examined in a specific company through interviews and survey. Recommendations for potential improvement based on the results of the research can also be found in the second part.
Vedoucí práce: Zuzana Křečková Kroupová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses